Analysis of Farming Group Member Participation on the Development Farming in Wonosoco Village Undaan District (Case Study of Waduk Rejo Farmers Group) - Muhammad Aris Pujiyanto; Nova Laili Wisuda; Garist Sekar Tanjung (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2023)
The farmer group's success is determined by the management's ability to manage the group and the group member's participation level. The group member's participation in activities organized by farmer groups should start from three stages. There are the planning stage, the implementation stage, and the monitoring stage. This research aimed to determine the group member's participation level in the Waduk Rejo farmer groups. This research was carried out in October 2022 in Wonosoco Village, Undaan District, Kudus Regency. Researchers used a quantitative descriptive research method with primary data types obtained through direct interview techniques with administrators and members of farmer groups. The sampling method was determined using the stratified proportional random sampling method, which consisted of 30 respondents, management, and members of the Waduk Rejo farmer groups. The variables studied were participation variables in the three stages: planning, implementation, and supervision. This study uses a Likert scale as a method of analysis. The findings show that the level of participation of farmer group members is manifested from the activity planning stage, which includes participation in routine farmer group meeting activities, participation in providing advice and input to farmer groups, and participation in preparing work plans of farmer groups which are included in the active category. The implementation phase, which provides for the participation of farmer group activities in the form of irrigation improvements, agricultural infrastructure improvements, and pest control, is included in the active category. The supervision phase, which provides for the supervision of irrigation repair activities, agricultural infrastructure improvement, and pest control, is included in the dynamic type. This research shows that the members of the farmer group have high awareness and concern to develop and advance their farmer group together.